Apparel Design Criteria: Anthropometric Measurement on Standard Sizing for Elderly Women with Physical Disabilities - Jamian, Juliza; Shaari, Nazlina (International Journal of Psychosocial Rehabilitation, 2020)
Smart apparel design considers an anthropometric measurement of normal sizing as significant criteria for the elderly people with disabilities. Stroke or half body paralysis is the prevalent condition sufferers experience and this group appears to have trouble moving through their everyday life due to changes on their body. The aim of this study is to establish standard sizing chart that follows the correct proportion of elderly women with disabilities. A case study was performed in Kajang, Malaysia, at Old Folks Home Centre. In this case, three different sizes of the body with the same state of illness were examined and analysed. It is for the elderly women to obtain an exact standard scale. The aim of this standard sizing study is to produce the correct body sizing chart for the elderly disabled age 65 and above. As a result, this anthropometric measurement provides a standard body sizing chart for elderly women with disabilities that can be used in the development of functional apparel product for another stage of the design process.